Due-window assignment scheduling with past-sequence-dependent setup times - Liu, Weiguo; Wang, Xuyin; Wang, Xiaoxiao; Zhao, Peizhen (Mathematical biosciences and engineering : MBE, 2022)
This article investigates the due-window assignment scheduling problem with setup times on a single machine, where setup times of jobs are past-sequence-dependent. Under common, slack and unrestricted due-window assignment methods, the goal is to determine the optimal job sequence and due-window such that the cost function (i.e., the weighted sum of earliness and tardiness, number of early and tardy jobs, due-window starting time and size) is minimized. We solve the problem optimally by introducing a polynomial time algorithm. An extension to the problem with learning and deterioration effects is also studied.